Future proofing mobile game advertising inventory : How mobile game companies can mitigate advertising revenue losses resulting from a tightening privacy landscape - Isto, Launo (My University, 2025)
Along with the smartphone revolution, mobile gaming industry has grown rapidly. Currently most mobile games are free to download from a smart device’s own application store. This has been made possible by shifting the monetization of users from the purchase required to download the app, to in-app purchases and showing advertising within the game. Currently mobile game advertising revenues are over a hundred billion USD annually, and this monetization method allows mobile game companies to financially benefit from their game while keeping it free for the users. Mobile game advertising has gone through significant privacy changes within the past years. Operating system side privacy initiatives like Apple’s App Tracking Transparency (ATT) framework and legal privacy requirements like IAB’s Transparency & Consent Framework (TCF) have restricted player data sharing to third parties. A vital part of this player data are device identifiers, which advertisers use for targeting advertising. These signal losses have made it increasingly hard for advertisers to target players, which has negatively affected their willingness to pay for impressions. With Google also having planned their Android Privacy Sandbox initiative for years, the digital advertising industry is preparing for additional signal losses, which are expected to further decrease impression prices, and thus decreasing advertising inventory value for mobile game companies. This thesis aims to find solutions, which mobile game publishers could use to mitigate these advertising revenue losses, while remaining compliant with the required privacy restrictions. A key enabler for this is first-party data that mobile game companies can directly collect from their players and can be used in a privacy compliant way for advertising targeting. This thesis examines the different parties involved within the mobile game advertising ecosystem, and how the mobile gaming industry together with the advertising industry could unlock additional value for both mobile game companies through higher impression prices, and advertisers through better targeting methods.

Älypuhelimien vallankumouksen myötä mobiilipeliteollisuus on kasvanut nopeasti. Nykyään suurin osa mobiilipeleistä ovat ilmaiseksi ladattavissa älylaitteen omasta sovelluskaupasta. Tämän on mahdollistanut rahan liikkumisen siirtyminen pelien lataushetkillä tapahtuvista ostoista pelinsisäisiksi ostoiksi ja mainosten näyttämiseksi peleissä. Tällä hetkellä mobiilipelien sisäisen mainonnan arvo on yli sata miljardia Yhdysvaltain dollaria vuodessa. Tämä kaupallistamiskeino mahdollistaa mobiilipeliyhtiöiden tehdä voittoa peleistään pelin ollessa ilmainen käyttäjille. Mobiilipelimainonta on läpikäynyt huomattavia yksityisyyteen liittyviä muutoksia viime vuosien aikana. Käyttöjärjestelmäpuolen yksityisyysaloitteet, kuten Applen App Tracking Transparency (ATT) -viitekehys ja lainsäädännölliset vaatimukset, kuten IAB:n Transparency & Control Framework (TCF) -viitekehys ovat rajoittaneet pelaajadatan jakamista kolmansille osapuolille. Tärkeä osa tätä pelaajadataa ovat laitetunnisteet, joita mainostajat käyttävät mainonnan kohdentamiseen. Näiden signaalien menetykset ovat heikentäneet entisestään mainostajien kykyä kohdentaa mainoksia pelaajille, mikä on vaikuttanut negatiivisesti mainostajien haluun maksaa mainosten näyttökerroista. Lisäksi Googlen olleen suunnittelemassa Android Privacy Sandbox aloitetta vuosia, digimainonnan toimialalla valmistaudutaan lisääntyviin signaalien menetyksiin, joiden oletetaan laskevan mainosten näyttökertojen hintoja entisestään, ja täten alentavan myös mobiilipeliyhtiöiden mainosinventaarion arvoa. Tämä opinnäytetyö pyrkii löytämään keinoja, joiden avulla mobiilipeliyhtiöt voivat lievittää mainosinventaarion arvon menetyksiä, samalla noudattaessaan yksityisyyteen liittyviä rajoituksia. Tärkeimpänä mahdollistajana on ensimmäisen osapuolen data, jota mobiilipeliyhtiöt voivat kerätä suoraan käyttäjiltään, ja käyttää sitä yksityisyysvaatimuksia noudattaen mainonnan kohdentamiseen. Opinnäytetyössä tutkitaan eri osapuolia, jotka liittyvät mobiilipelimainonnan ekosysteemiin, ja kuinka mobiilipeliteollisuus voi yhdessä mainosteollisuuden kanssa saada lisäarvoa mobiilipeliyhtiöille korkeampien mainosten näyttökertojen hintojen kautta, ja mainostajille parempien kohdennuskeinojen kautta.
Keywords: Mobile game advertising, Data privacy, First-party data, mobiilipelimainonta, tietosuoja, ensimmäisen osapuolen data